VALUATION OF INVENTORIES. - Broad, Samuel J. (The Accounting Review, 1950)
Abstract For an industrial or mercantile company the proper determination of its inventory is probably the most difficult part of its periodical accounting. It is also the most important, because of the impact which inventories have upon both the balance sheet and the income statement. Historically, and largely because of credit requirements, the balance sheet was considered of relatively greater importance than it is today, and one of the approved concepts for inventory determination was that it should be stated on a conservative basis. The Committee on Accounting Procedure of the American Institute of Accountants has stated that in accounting for the goods in the inventory "the major objective is the matching of appropriate costs against revenues in order that there may be a proper determination of realized income." Although the cost basis usually results in a proper matching of costs and revenues, nevertheless there are circumstances under which cost may not be the amount properly chargeable against the revenues of future periods.